(untitled) (Acta Scientiarum. Health Sciences, 2017)
This study aimed to evaluate the risk of developing pressure ulcers (PU) and related factors in elderly residents in LTI of a medium-sized municipality in southern Brazil. The method applied was a cross-sectional study with elderly residents in a long-term institution (LTI) in Brazil, using sociodemographic questionnaire, health conditions questionnaire and Braden Scale. The data was analyzed using descriptive and inferential statistics. The results showed that most seniors had some degree of risk (57.2%) to develop PU, but no elderly presented the condition. Among the elderly at risk for PU, 54.5% of them rate their health as good, 46.7% participate in activities and 52.6% are satisfied with the institution. Conclusions: The absence of PU and positive evaluations of the elderly may be a result of the care offered by the LTI. The Braden Scale is an instrument that enables the planning and implementation of actions to improve the health of institutionalized elderly.